POTENSI VIRTUAL REALITY (VR) SEBAGAI MEDIA PEMBELAJARAN MUKHTAKHIR DALAM PENDIDIKAN AGAMA ISLAM (STUDI KASUS SMK MUHAMMADIYAH 1 BANTUL) - Pratama, Bagaskara Nanda; Roihan, Rifqi Aji (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
The development of digital technology has encouraged the emergence of Virtual Reality (VR) as an advanced learning medium with the potential to provide immersive learning experiences, including in Islamic Religious Education (IRE), which emphasizes the understanding of values, religious practices, and the internalization of spiritual meaning. This study aims to analyze the potential use of VR as a learning medium in IRE and to identify the opportunities and challenges of its implementation at SMK Muhammadiyah Bantul. This research employs a descriptive qualitative approach, with data collected through classroom observations, in-depth interviews with IRE teachers and students, and documentation of technology-based instructional materials. The findings indicate that VR has significant potential to enhance learning motivation, strengthen students’ conceptual and contextual understanding of IRE content, and support the visualization of abstract materials such as Islamic history, Hajj rituals simulation, and moral values. However, the implementation of VR still faces constraints, including limited infrastructure, teachers’ technological competence, and the need to adapt learning materials to ensure alignment with Islamic pedagogical and spiritual values. This study concludes that Virtual Reality can serve as an innovative and effective learning medium for Islamic Religious Education when supported by adequate infrastructure readiness, improved teachers’ digital literacy, and the strengthening of teachers’ roles in guiding students so that the use of technology remains grounded in Islamic values.ABSTRAKPerkembangan teknologi digital mendorong hadirnya Virtual Reality (VR) sebagai media pembelajaran mutakhir yang berpotensi memberikan pengalaman belajar imersif, termasuk dalam Pendidikan Agama Islam (PAI) yang menekankan pemahaman nilai, praktik ibadah, dan internalisasi makna spiritual. Penelitian ini bertujuan untuk menganalisis potensi pemanfaatan VR sebagai media pembelajaran PAI serta mengidentifikasi peluang dan tantangan implementasinya di SMK Muhammadiyah Bantul. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode pengumpulan data melalui observasi kegiatan pembelajaran, wawancara mendalam dengan guru PAI dan peserta didik, serta dokumentasi perangkat pembelajaran berbasis teknologi. Hasil penelitian menunjukkan bahwa VR memiliki potensi besar dalam meningkatkan motivasi belajar, memperkuat pemahaman konseptual dan kontekstual materi PAI, serta membantu visualisasi materi abstrak seperti sejarah Islam, manasik haji, dan nilai-nilai akhlak. Namun demikian, implementasi VR masih menghadapi kendala berupa keterbatasan sarana prasarana, kompetensi guru dalam penguasaan teknologi, serta perlunya penyesuaian materi agar selaras dengan nilai-nilai pedagogik dan spiritual Islam. Penelitian ini menyimpulkan bahwa Virtual Reality dapat menjadi media pembelajaran PAI yang inovatif dan efektif apabila didukung oleh kesiapan infrastruktur, peningkatan literasi teknologi guru, serta penguatan peran guru dalam membimbing peserta didik agar pemanfaatan teknologi tetap berlandaskan nilai-nilai keislaman.